Evaluation of the Effectiveness of Online Training on the Recommendation Intention of Port Employees in Indonesia - Ika Yulianti; Sa’diyah El Adawiyah; Oskar Vitriano; Deva Lestari; Richard Frimpong (CV. RADJA PUBLIKA, 2026)
This study aims to evaluate the effectiveness of online training on the recommendation intention of port employees in Indonesia. The research employed a quantitative approach using a survey method. The population consisted of 181 employees who had participated in online training programs, and saturated sampling was applied, involving the entire population as respondents. Data were collected through a Likert-scale questionnaire (1–5) and analyzed using SPSS version 29. The analysis included validity and reliability tests, classical assumption tests, multiple linear regression, t-test, and F-test. The results indicate that perceptions of training components simultaneously have a significant effect on recommendation intention (F-test, p < 0.05). However, the coefficient of determination (R² = 0.131) shows that these variables explain only 13.1% of the variance in recommendation intention. Partially, perceived trainer quality has a significant positive effect, while perceived benefits show a significant negative effect. Perceptions of training materials and facilities do not significantly influence recommendation intention. These findings highlight the crucial role of trainer competence in shaping employees’ willingness to recommend online training programs. The study suggests that training providers should focus on improving trainer quality and managing participants’ expectations regarding training benefits. Future research is recommended to incorporate additional variables such as satisfaction, loyalty, and organizational support to develop a more comprehensive predictive model.